PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL (GROUP SORT) DALAM PEMBELAJARAN SEJARAH TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Habibah Habibah; Heri Susanto; Dewicca Fatma Nadilla; Helmi Akmal (Lambung Mangkurat University, 2025)
History learning is often perceived as tedious, accompanied by students’ low critical thinking skills. In the digital era, critical thinking is an essential competence for filtering information and countering misinformation. One innovative instructional medium that can be employed is Wordwall (group sort), which is designed to create a more interactive and participatory learning experience. This study aims to analyze the effect of using Wordwall (group sort) on students’ critical thinking skills in history learning. The research was conducted at SMAN 12 Banjarmasin during the first semester of the 2024/2025 academic year, employing a quasi-experimental method with a posttest-only control group design. The study population comprised 188 eleventh-grade students, with a sample of 62 students selected through purposive sampling and divided into an experimental class (XI-1) and a control class (XI-2). The research instrument consisted of five validated essay test items. Data were analyzed using normality, homogeneity, and t-tests with the assistance of IBM SPSS 29. The results indicated that the calculated t-value (2.259; df = 60) exceeded the critical t-table value (2.000) at a significance level of 0.028 < 0.05. These findings demonstrate a significant effect of Wordwall (group sort) on students’ critical thinking skills. Therefore, Wordwall proved to be more effective than PowerPoint, as evidenced by the higher posttest mean scores of the experimental class compared to the control class.